Face Masks Use and Its Role in Restraining the Spread of COVID-19 Pandemic in Saudi Arabia: Knowledge, Attitude, and Practices Based Cross-Sectional Study - Meo, Sultan Ayoub; Alqahtani, Sara A.; Aljedaie, Ghada M.; Binmeather, Fatimah S.; AlRasheed, Renad A.; Albarrak, Raghad M. (Frontiers in Public Health, 2022)
Abstract Face masks (FM) play a role in limiting the spread of viral infections; despite this, their role is influenced by the population's adherence to wearing the FM. However, the impact on the effectiveness of the FM is variable in various communities. This study aimed to investigate the knowledge, attitude, and practices towards FM use during COVID-19 in Saudi Arabia. This observational "cross-sectional questionnaire-based" study was conducted from September 8 to 21, 2021. The data was collected using an online questionnaire survey during the COVID-19 pandemic. The questionnaire was distributed via social media platforms, WhatsApp, to assess the knowledge, attitude, and practices using single choice questions and a five-point Likert scale. The questionnaire was distributed to 1356 people, and the participant's response rate was 678 (50%). Among them 207 (30.5%) were males and 471 (69.5%) females. Among the participants, Saudi citizens were (649; 95.7%), with university education (502; 74%) and were mostly (368; 54.3%) between 16 to 24 years of age. The participants (384; 56.6%, p < 0.001) had good knowledge about face masks, and more than half of the respondents, 531 (78.3%) (p < 0.001), showed a positive attitude. Most of the respondents (477, 70.2%) believed that everyone could use the face mask to minimize the spread of the disease; however, (111; 16.4%) reported that they would not wear a face mask if the government did not recommend wearing it in public places during the COVID-19 pandemic. Saudi citizens have above-average knowledge and optimistic attitudes towards using face masks during the COVID-19 pandemic. The community is convinced about the face masks and believes that face masks play a predominant role in limiting the spread of SARS-CoV-2.